Strengthening Spiritual Values through Environmental Physics Learning Assisted by Authentic Data Modelling and Visual Media - Johan, Henny; Mayub, Afrizal; Wardana, Rendy Wikrama; Herawati, Asmida; Sudirman, Sudirman; Noviana, Noni; Umaya, Umaya (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2024)
Environmental Physics concepts are very likely to be explored to facilitate the cultivation of spiritual attitudes because they are closely related to phenomena in everyday life. Visual media can help visualize environmental phenomena so that they are easier to understand. This study aims to instill spiritual values through the concept of Environmental Physics as an alternative learning that focuses on the affective domain with the help of visual media. This study involved 15 science education postgraduate students. This research used a Pre-experimental design with a Shoot Case Study. The research design includes pre-experiment, experiment, and analysis of experimental data results. In the pre-experiment stage, the concept of environmental physics and spiritual attitudes were analyzed, learning tools were prepared, and questionnaire instruments for student perceptions related to the cultivation of spiritual values were prepared. At the experimental stage, the implementation of Environmental Physics learning integrated with spiritual values was carried out. In the post-experiment stage, data analysis and interpretation were carried out to answer research problems. Based on the results of data analysis, it is known that 92.15% of respondents strongly agree that learning environmental physics can instill awareness of the nature of God. Based on the results of the open-ended questionnaire, it is known that students can explain the content of spiritual values in various phenomena in the environment. In addition, students stated that visual media can facilitate the activity of instilling awareness that God is omnipotent over all the universe. Thus it can be concluded that environmental physics learning activities can instil spiritual attitudes through environmental physics content assisted by visual media. Science content, especially environmental physics, is very relevant in instilling spiritual values